Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

In "Introduction to Calculus and Analysis" pages 221-223 Courant derives the following for an implicit function F(x,y)=0. Using

$dF = F_x dx + F_y dy = 0$

$dy = \frac{dy}{dx} dx = -\frac{F_x}{F_y}dx$

Also $y' = -\frac{F_x}{F_y}$

He says $f(x) = y$ therefore

$y' = \frac{F_x(x,f(x))}{F_y(x,f(x))}$

What I don't understand is, when I derived $y''$ using the Quotient Rule

$y'' = -\frac{F_yF_{xx}f' - F_xF_{yx}f'}{F_y^2}$

in the book however the result is

$y'' = - \frac{F_yF_{xx}+F_yF_{xy}f' - F_x F_{xy} - F_x F_{yy}f'}{F_y^2}$

I dont understand how the extra terms were derived.


share|cite|improve this question
up vote 1 down vote accepted

It is just the Chain Rule. When deriving the numerator with respect to $x$ we get: $$ \frac{\partial}{\partial x}F_x(x,f(x))=\frac{\partial F_x}{\partial x}(x,f(x))+\frac{\partial F_x}{\partial y}\frac{df}{dx}=F_{xx}(x,f(x))+F_{xy}(x,f(x))f'(x). $$ Similarly, $$ \frac{\partial}{\partial x}F_y(x,f(x))=F_{xy}(x,f(x))+F_{yy}(x,f(x))f'(x). $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.